Investigating the Relationship Between the World Giving Index and the Donations in Lions Clubs International Foundation - Mária Murray Svidronova; Alena Kaščáková; Bohumír Krátky (Institutiones Administrationis, 2024)
There is much research on how to improve the provision of local public services without having to increase municipal public spending. Latest trends stress out the role of citizens and non-governmental organizations (NGOs) that can provide various public services using private funding (donations) and volunteers. This paper analyses the relationship between the World Giving Index and donation in a selected NGO, the Lions Clubs International Foundation (LCIF). We investigate whether financial donations made to international humanitarian LCIF in different countries around the world influence the World Giving Index. Main methods used are panel regression and correlation analysis on the sample of 97 countries and 116,033 donors. The results suggest that donations made to LCIF have a positive impact on the World Giving Index. We support our findings with extended theory of planned behaviour model for Slovakia based on a questionnaire with 150 respondents.